2013
DOI: 10.1007/s00125-013-3026-6
|View full text |Cite
|
Sign up to set email alerts
|

Does metformin modify the effect on glycaemic control of aerobic exercise, resistance exercise or both?

Abstract: Aims/hypothesis Some previous studies suggested that metformin might attenuate the effects of exercise on glycaemia or fitness. We therefore examined whether metformin use influenced changes in glycaemic control, fitness, body weight or waist circumference resulting from aerobic and/or resistance training in people with type 2 diabetes participating in an exercise intervention trial. Methods After a 4 week run-in period, participants from the Diabetes Aerobic and Resistance Exercise (DARE) trial were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 8 publications
4
42
0
Order By: Relevance
“…3). However, metformin showed no significant interaction with exercise in a study of the long-term effect of exercise in type 2 diabetes wherein no additional improvement in HbA 1c was seen in the metformin-treated group compared with the group not treated with metformin (31).…”
Section: Discussionmentioning
confidence: 94%
“…3). However, metformin showed no significant interaction with exercise in a study of the long-term effect of exercise in type 2 diabetes wherein no additional improvement in HbA 1c was seen in the metformin-treated group compared with the group not treated with metformin (31).…”
Section: Discussionmentioning
confidence: 94%
“…No patient reported changing in his dose of medication during the study. Though, recent study showed that metformin did not significantly attenuate the benefits of exercise on glycemic control or fitness [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Although most of the studies have proposed that metformin is beneficial for muscle function, recent studies that have evaluated the effects of metformin on aerobic capacity have found a reduction in aerobic capacity with metformin treatment, suggesting that metformin might be attenuating exercise‐induced benefits on insulin sensitivity and cardio‐metabolic health . Another study, however, noted that there was no metformin‐mediated attenuation of exercise benefits on glycemic control …”
Section: Drugs and Musclementioning
confidence: 99%